Estimation of Edamame Flour Shelf Life Using the Critical Moisture Approach - Ahmad Maulana Fikri Handoyo; Ulya Sarofa (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
This research aimed to estimate the shelf life of edamame flour products using the Accelerated Shelf Life Testing (ASLT) with the critical moisture content approach in various types of packaging. This research was conducted in two stages, the first stage was in the process of making flour, then the second stage was estimating the shelf life. Shelf life estimation was carried out with two repetitions on three different types of packaging materials, those are polypropylene plastic, metalized plastic and aluminum foil. Then the data obtained will be analyzed utilizing simple linear regression using Microsoft Excel. Based on the results of estimating shelf life using the critical moisture content approach, it can be seen that edamame flour with polypropylene plastic packaging has a shelf life of 172 days, metalized plastic packaging has a shelf life of 585 days, and aluminum foil packaging has a shelf life of 229 days. Based on research results, it can be seen that the critical moisture content affects the shelf life of edamame flour and the best packaging for storing edamame flour is using metalized plastic packaging.